Pemanfaatan Teknologi Komunikasi SPADA UNTIRTA Dalam Meningkatkan Aktivitas Belajar - Azahra Magdataura Bani Agung; Nina Yuliana (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research discusses the use of SPADA Untirta communication technology in increasing learning activities. SPADA Untirta is an online learning system implemented at Sultan Ageng Tirtayasa University (UNTIRTA) to make it easier for Untirta students to learn both face to-face and online. SPADA Untirta has many benefits in increasing student learning activities. However, despite the many benefits that SPADA has, there are several things that can hinder the use of SPADA. The aim of this research is to determine the use of SPADA Untirta communication technology in improving learning activities and to find out what obstacles and things cause the use of SPADA Untirta to be hampered. The method that researchers used in this research is a qualitative research method. The technique that the researcher uses in this research is a phenomenological study research technique where the researcher wants to understand the direct experience of the person being studied. Phenomenological studies focus on in-depth descriptions of how individuals experience a phenomenon or event. In this research, researchers used phenomenological theory. This theory emphasizes a deeper understanding of the life experiences of individuals or groups and observing the meaning of the phenomena they experience.